(99m)Tc-bioorthogonal click chemistry reagent for in vivo pretargeted imaging - García, María Fernanda (Bioorg Med Chem, 2016)
Metal-free click chemistry has become an important tool for pretargeted approaches in the molecular imaging field. The application of bioorthogonal click chemistry between a pretargeted trans-cyclooctene (TCO) derivatized monoclonal antibody (mAb) and a (99m)Tc-modified 1,2,4,5-tetrazine for tumor imaging was examined in vitro and in vivo. The HYNIC tetrazine compound was synthesized and structurally characterized, confirming its identity. Radiolabeling studies demonstrated that the HYNIC tetrazine was labeled with (99m)Tc at an efficiency of >95% and was radiochemically stable. (99m)Tc-HYNIC tetrazine reacted with the TCO-CC49 mAb in vitro demonstrating its selective reactivity. In vivo biodistribution studies revealed non-specific liver and GI uptake due to the hydrophobic property of the compound, however pretargeted SPECT imaging studies demonstrated tumor visualization confirming the success of the cycloaddition reaction in vivo. These results demonstrated the potential of (99m)Tc- HYNIC-tetrazine for tumor imaging with pretargeted mAbs.